A Model Of Strategic Information System Planning (Sisp) Approach Determination - Harini (2001)
The importance of corporate planning in guiding a strategic information system process has been commonly advocated in both prescriptive and empirical research. Strategic Information System Planning (SISP) are increasingly modeled after corporate plans, as more and more companies seek to leverage Information Technology (IT) to compete more effectively in the globalized world. Despite the heightened interest and activity associated with the topic, there is a range of opinion regarding what should constitute in an SISP approach. Therefore this study attempts to propose a model to determine the SISP approach determination and it's relation to the internal factors of an organization , using Information Systems as a strategic planning to gain the competitive advantage. The model of the SISP approach determination in this study is tested in three different types of Malaysian organizations; education, service and telecom munication namely Universiti Putra Malaysia,